Effects of qualitative feed restriction on compensatory growth in the broiler chicken - Mazzuco, Helenice; Guidoni, Antonio Lourenço; Jaenisch, Fátima Regina (Pesquisa Agropecuaria Brasileira, 2000)
An experiment was conducted to determine the effects of the diet dilution on performance of broiler chickens until 42 days of age. Nutrient restriction was achieved by feeding a starter diet (CP 21.5% and ME 3,050 kcal/kg) in which the major ingredients were replaced with 25% or 50% of soybean hulls. Four treatments involved feeding the diluted diets for seven days (7-14 days of age), either continuous or split into periods with the undiluted diet (control). The treatments were: T1: control diet; T2 and T3: diluted diet (25% and 50% of soybean hulls, respectively) 7-14 days; T4 and T5: diluted diet (25% and 50% of soybean hulls, respectively) on days 7, 9, 11 and 13 alternating with T1 (on days 8, 10 and 12). The birds fed with diluted diets exhibited lower mean body weights (P < 0.05) than controls. Feed conversion ratios from 0-42 days of age for restricted broilers were not different. Varying the period of nutrient restriction did not affect adversely body weight and body weight gain. There was no statistical difference in the overall mortality through 0-42 days among the dietary treatments. Compensatory growth was not observed, and this result could be associated with the pattern of growth curve exhibited by the hybrids used in this experiment.